Laparoscopic-assisted Open Surgery for Bochdalek Hernia with Gastric Volvulus Involving Multiple Organs: A Case Report - Yang, Xinxi; Li, Shihong; Nie, Pan; Liu, Kehao; Hou, Kang (Journal of clinical and diagnostic research, 2025)
Bochdalek hernias are a rare form of diaphragmatic hernia that are usually asymptomatic and typically observed in children. In adults, they are rare and often detected incidentally through imaging. Acute gastric torsion is an uncommon condition in clinical practice, and without timely intervention, life-threatening complications such as gastric strangulation, perforation, and shock may ensue. This case report describes a 74-year-old female patient who presented with abdominal pain and bloating. Following a physical examination and Computed Tomography (CT) scan, the patient was diagnosed with gastric volvulus due to a left Bochdalek hernia. The stomach, spleen, colon, and left kidney were also affected. The patient underwent a successful laparoscopic-assisted open surgical procedure, showing a positive recovery with no complications, and was discharged one week after the operation. At the six-month follow-up, there were no signs of hernia recurrence or other discomfort. During the surgical procedure, it was ascertained that the patient exhibited organ-axial gastric torsion, a condition characterised by the rotation of the stomach around the axis connecting the pylorus and the oesophageal junction. The combination of Bochdalek hernia with gastric volvulus obstruction represents a rare clinical entity, particularly when complicated by the involvement of multiple organs within the hernial sac. Any therapeutic delay in such cases may result in organ necrosis and potentially fatal outcomes. This case emphasises the necessity for meticulous diagnostic and management strategies for Bochdalek hernias, particularly in instances involving multiple organs, to avert complications such as organ necrosis.